TRANSFORMASI PENGELOLAAN PRODUK UNGGULAN DESA MANATANG KECAMATAN ABAD SELATAN KE PASAR GLOBAL - Petrus Mau Tellu Dony; Oktovianus Sandy, Indriyani Anastasia Lalang sir, Defi Kepa, Lia Veronika Koilbain, Ledi A. Koilmo, (JOURNAL OF COMMUNITY DEDICATION, 2025)
Manatang Village community in July 2025. The results showed that there were three main superior products developed: chocolate and balado banana chips, pure candlenut oil, and KU-HE-SE (Turmeric-Ginger-Lemongrass) herbal medicine. The production process for each product is described in detail, from raw material processing to packaging. In addition, this study highlights the strategic role of outreach and training conducted by students for the community, PKK members, youth, and junior high school students. This training successfully increased community skills and awareness in managing local natural resources into high-value products. Collaboration with the village government and participation in the Village Guard outreach also demonstrate the integration of the KBPM program with local development policies. Digital marketing efforts through social media (Facebook, Instagram, WhatsApp) were implemented to expand market reach to the global level. Overall, this study concludes that the KBPM program which focuses on local product development, skills improvement, and digital technology utilization is an effective model for community empowerment and improving the economic welfare of Manatan Village, South Abad District